Optimizing Inter-Site Traffic Comparative Performance Analy-sis of IPSec with IKEv2 RSA-ESP and IKEv2 with PSK - Surya Pratama; Mohammad Ramaddan Julianti; Detin Sofia (Jurnal Teknologi Informasi dan Multimedia, 2025)
This study compares the performance of IPsec VPNs using Internet Key Exchange version 2 (IKEv2) with RSA and Pre-Shared Key (PSK) authentication. The research is driven by the rising need for secure and efficient communication in distributed systems, particularly in environments with limited resources and sensitivity to latency. Guided by the PPDIOO framework, this study assesses system performance across two distinct scenarios: standard operational conditions and impaired (stressed) network environments. Key metrics include latency, jitter, throughput, packet loss, and IKE negotiation time, measured using iperf3, ping, and tc netem. The testbed uses virtual Ubuntu environments with strongSwan 5.9.13 on VMware® Workstation, simulating inter-site traffic VPNs. Under normal conditions, PSK outperforms RSA by showing lower latency (0.82 ms vs. 0.88 ms), faster IKE setup (10.05 ms vs. 20.80 ms), and higher UDP throughput. Under stressed conditions—100 ms latency, 20 ms jitter, and 1% packet loss—PSK remains more resilient, especially for real-time UDP traffic. RSA offers steady performance for TCP downloads. Statistical significance is confirmed using paired t-tests. The results suggest PSK suits lightweight deployments with minimal cryptographic demands, while RSA is better for environments requiring certificate-based security. This study provides valuable insights for network architects in selecting appropriate IPsec configurations based on specific operational requirements. Future research may explore scalability considerations, multi-user environments, and the integration with Software-Defined Wide Area Networking (SD-WAN) technologies.